2015
DOI: 10.1038/srep18135
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Mediated Laser Ablation under Ambient Conditions for Spatially-Resolved Tissue Proteomics

Abstract: Numerous applications of ambient Mass Spectrometry (MS) have been demonstrated over the past decade. They promoted the emergence of various micro-sampling techniques such as Laser Ablation/Droplet Capture (LADC). LADC consists in the ablation of analytes from a surface and their subsequent capture in a solvent droplet which can then be analyzed by MS. LADC is thus generally performed in the UV or IR range, using a wavelength at which analytes or the matrix absorb. In this work, we explore the potential of visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…However, the intensities accessible via the 55 fs and 56 ps pulses result in a high photon density capable of driving nonresonant, multiphoton absorption to overcome the band gap of quartz or couple into the molecular system of the myoglobin . Previous studies have shown that no mass spectral signal for bradykinin or phosphocholine was achieved from silica glass using a ns pulse with laser pulse energies from 0 to 2.4 mJ without the addition of a resonantly absorbing matrix . Regardless of wavelength, the efficiency of ns laser ablation relies upon the presence of a resonance within the sample or substrate .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the intensities accessible via the 55 fs and 56 ps pulses result in a high photon density capable of driving nonresonant, multiphoton absorption to overcome the band gap of quartz or couple into the molecular system of the myoglobin . Previous studies have shown that no mass spectral signal for bradykinin or phosphocholine was achieved from silica glass using a ns pulse with laser pulse energies from 0 to 2.4 mJ without the addition of a resonantly absorbing matrix . Regardless of wavelength, the efficiency of ns laser ablation relies upon the presence of a resonance within the sample or substrate .…”
Section: Resultsmentioning
confidence: 99%
“…A similar saturation in the mass spectral signal was observed in the 532 nm, 4 ns laser ablation energy optimization of aqueous bradykinin peptide, phosphatidyl choline, and lysozyme C protein from stainless-steel substrates. 42 At the highest power tested, the 55 fs pulse shows an increase in signal intensity with a large standard deviation (305.0 ± 232.6), while a decrease in signal was observed for the 56 ps pulse (58.0 ± 2.1). Previous investigations showed that comparable mass spectral signal intensities for absorbing (∼10 3 cm −1 ) and nonabsorbing (∼0.2 cm −1 ) analytes were similar when using equivalent laser fluences from stainless-steel substrates.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of material by laser ablation/droplet capture was demonstrated in a spatially resolved proteomics strategy [71]. When combined with a nanoPOTS workflow, hundreds of proteins were identified from 50 μm diameter laser-dissected tissue samples; however, the workflow inherently relies on enzymatic digestion and liquid chromatography separation to achieve these numbers.…”
Section: Desorption Techniquesmentioning
confidence: 99%